Titanium-Based Biomaterials for Preventing Stress Shielding between Implant Devices and Bone - M. Niinomi; M. Nakai (International Journal of Biomaterials)
β-type titanium alloys with low Young's modulus are required to inhibit bone atrophy and enhance bone remodeling for implants used to substitute failed hard tissue. At the same time, these titanium alloys are required to have high static and dynamic strength. On the other hand, metallic biomaterials with variable Young's modulus are required to satisfy the needs of both patients and surgeons, namely, low and high Young's moduli, respectively. In this paper, we have discussed effective methods to improve the static and dynamic strength while maintaining low Young's modulus for β-type titanium alloys used in biomedical applications. Then, the advantage of low Young's modulus of β-type titanium alloys in biomedical applications has been discussed from the perspective of inhibiting bone atrophy and enhancing bone remodeling. Further, we have discussed the development of β-type titanium alloys with a self-adjusting Young's modulus for use in removable implants.